Transition from Secondary School to Medical School: The Role of Self-Study and Self-Regulated Learning Skills in Freshman Burnout - Barbosa, Joselina (2016)
Introduction: The transition from secondary to higher education is a challenging and demanding period for medical students. The ability to manage study time effectively and to be a self-regulated learner is essential to cope with the exponential growth of knowledge in medical education. Thus, the purpose of our study was to measure self-regulated learning skills and self-study across secondary higher education transition and to explore its effect on academic burnout in the first year of medical school.Material and Methods: We collected data from 102 (43%) freshman medical students on self-regulated learning, academic achievement, and hours of self-study/week relative to last year of secondary school (at the beginning of academic year) and the first year of medical school (at the end of academic year). Burnout data was collected at the end of academic year.Results: Among the 102 participants, 12% were at risk of burnout. Self-directedness at secondary school and higher education, and strategies for learning and assessment at higher education were protective factors against academic burnout. However, secondary selfdirectedness has an indirect effect on academic burnout mediated by self-directedness in the first year of medical school. In addition, self-study during class period was a risk factor for burnout.Conclusion: Our results support the premise that students experience mental health problems from an early stage at medical school. Empowering medical students to develop strategies for learning assessment and self-direction will help them manage their learning and, consequently, promote their well-being. Finally, we found that it is not academic performance that influences burnout but the time dedicated to study.